Cervical musculoskeletal impairment in frequent intermittent headache. Part 1: Subjects with single headaches - Jull, G; Amiri, M; Bullock-Saxton, J; Darnell, R; Lander, C (Cephalalgia, 2007)
Musculoskeletal disorders are considered the underlying cause of cervicogenic headache, but neck pain is commonly associated with migraine and tension-type headaches. This study tested musculoskeletal function in these headache types. From a group of 196 community-based volunteers with headache, 73 had a single headache classifiable as migraine (n = 22), tension-type (n = 33) or cervicogenic headache (n = 18); 57 subjects acted as controls. Range of movement, manual examination of cervical segments, cervical flexor and extensor strength, the cranio-cervical flexion test (CCFT), cross-sectional area of selected extensor muscles at C2 (ultrasound imaging) and cervical kinaesthetic sense were measured by a blinded examiner. In all but one measure (kinaesthetic sense), the cervicogenic headache group were significantly different from the migraine, tension-type headache and control groups (all P < 0.001). A discriminant function analysis revealed that collectively, restricted movement, in association with palpable upper cervical joint dysfunction and impairment in the CCFT, had 100% sensitivity and 94% specificity to identify cervicogenic headache. There was no evidence that the cervical musculoskeletal impairments assessed in this study were present in the migraine and tension-type headache groups. Further research is required to validate the predictive capacity of this pattern of impairment to differentially diagnose cervicogenic headache.